Автоматизація вибору оптимальних проектних варіантів систем зв'язку на основі методів багатокритеріальної оптимізації - Чеботарьова, Д. В.; Безрук, В. М. (Lviv Polytechnic National University, 2022)
This paper is devoted to the problem of choosing the optimal design variant of communication systems, taking into account at a formalized level a set of conflicting requirements and a set of quality indicators. The article proposes to use the methods of multicriteria optimization to select the best options for communication systems: the method of discrete selection by the unconditional criterion of preference and the method based on the theory of utility. The method of choosing the optimal variant is presented, the example of solving the problem of choosing the optimal variant of the mobile communication system at the nominal stage of network planning is considered. To solve the problem of choosing the best design options by multicriteria optimization methods, a special program has been developed that automates the process of solving the problem of choosing the optimal solutions based on the use of multicriteria optimization methods.
Keywords: multicriteria optimization; quality index; communication systems